Case report: MSI-H, EGFR mutation, and ground-glass nodules as diffuse pulmonary hematogenous metastases - He, Liuer; Li, Lin (Frontiers in Immunology, 2024)
Key Result: 1. In lung adenocarcinoma, multiple ground-glass nodules can indicate hematogenous metastases rather than synchronous multiple primary lung cancers. 2. For lung adenocarcinoma patients with concurrent Microsatellite Instability-High, EGFR-sensitive mutation, and ground-glass metastatic lesions, treatment with EGFR-Tyrosine Kinase Inhibitors can achieve partial response but with a short progressionfree survival. 3. When a patient's symptoms and imaging findings significantly improve after treatment, a persistently elevated carcinoembryonic antigen level suggests occult metastasis and a poor prognosis.